Simultaneous adsorption of malachite green and methylene blue dyes in a fixed-bed column using poly(acrylonitrile-co-acrylic acid) modified with thiourea - Adeyi, Abel Adekanmi; Md. Jamil, Siti Nurul Ain; Abdullah, Luqman Chuah; Choong, Thomas Shean Yaw; Lau, Kia Li; Alias, Nor Halaliza (MDPI AG, 2020)
Proper remediation of aquatic environments contaminated by toxic organic dyes has become a research focus globally for environmental and chemical engineers. This study evaluates the adsorption potential of a polymer-based adsorbent, thiourea-modified poly(acrylonitrile-co-acrylic acid) (T-PAA) adsorbent, for the simultaneous uptake of malachite green (MG) and methylene blue (MB) dye ions from binary system in a continuous flow adsorption column. The influence of inlet dye concentrations, pH, flow rate, and adsorbent bed depth on adsorption process were investigated, and the breakthrough curves obtained experimentally. Results revealed that the sorption capacity of the T-PAA for MG and MB increase at high pH, concentration and bed-depth. Thomas, Bohart-Adams, and Yoon-Nelson models constants were calculated to describe MG and MB adsorption. It was found that the three dynamic models perfectly simulate the adsorption rate and behavior of cationic dyes entrapment. Finally, T-PAA adsorbent demonstrated good cyclic stability. It can be regenerated seven times (or cycles) with no significant loss in adsorption potential. Overall, the excellent sorption capacity and multiple usage make T-PAA polymer an attractive adsorbent materials for treatment of multicomponent dye bearing effluent in a fixed-bed column system.